2016
DOI: 10.1371/journal.pone.0164239
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Basal and Acute Autophagic Responses in the Adult Drosophila Nervous System: The Impact of Gender, Genetics and Diet on Endogenous Pathway Profiles

Abstract: The autophagy pathway is critical for the long-term homeostasis of cells and adult organisms and is often activated during periods of stress. Reduced pathway efficacy plays a central role in several progressive neurological disorders that are associated with the accumulation of cytotoxic peptides and protein aggregates. Previous studies have shown that genetic and transgenic alterations to the autophagy pathway impacts longevity and neural aggregate profiles of adult Drosophila. In this study, we have identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(66 citation statements)
references
References 85 publications
8
58
0
Order By: Relevance
“…The epitope used to generate GABARAP antibody has identical amino acid sequences to Drosophila Atg8a protein (personal communication with Cell Signaling Technology and see sequence alignment in Figure S2A). This antibody has been previously used in several Drosophila autophagy studies [25][26][27], and verified by Kim et al [28]. We further verified the specificity of the GABARAP antibody using an Atg8a loss-offunction mutant Atg8a Δ4 (Figure S2B-D).…”
Section: Antibodies and Immunostainingsupporting
confidence: 75%
“…The epitope used to generate GABARAP antibody has identical amino acid sequences to Drosophila Atg8a protein (personal communication with Cell Signaling Technology and see sequence alignment in Figure S2A). This antibody has been previously used in several Drosophila autophagy studies [25][26][27], and verified by Kim et al [28]. We further verified the specificity of the GABARAP antibody using an Atg8a loss-offunction mutant Atg8a Δ4 (Figure S2B-D).…”
Section: Antibodies and Immunostainingsupporting
confidence: 75%
“…Both human and model organism studies have shown even modest dietary modifications can have a significant positive influence on longevity and the health of aging individuals [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Existing research into the molecular mechanisms that underpin such improved health and longevity metrics indicates that the long-term function of multiple cellular systems is essential [ 3 , 5 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently characterized a mild intermittent fasting (IF) protocol that promotes longevity and neural function of middle-aged adult Drosophila strains from divergent genetic backgrounds [ 1 , 16 , 17 ]. The beneficial effects of this fasting protocol included a delay in the progressive decline of locomotor behaviors and a reduction in neural aggregate levels [ 1 , 16 , 17 ]. This was associated with improvements in the acute and long-term functions of the autophagy pathway within middle-aged fly neurons [ 1 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations